Resilience in adolescents following experience of sexual abuse : self-esteem as a mediator - Margrét S. Kaldalóns Sigurðard. 1999- (2021)
While sexual abuse has adverse consequences for victims, some, however, show a significant ability to maintain normal functioning in life or resilience. Studies on sexual abuse survivors indicate that different personal and environmental factors mediate the effect of sexual abuse on resilience. The aim of this study was to examine how sexual abuse affects resilience in adolescents and the mediating role of self-esteem. The study was conducted using a random sample of 2,129 adolescents studying at junior colleges in Iceland in 2016. The findings indicated that sexual abuse victims had significantly less resilience than non-victims. Self-esteem was positively correlated with resilience. Factorial analysis of covariance demonstrated that the relationship between self-esteem and resilience in sexual abuse victims interacts with gender. Overall, boys scored higher on the resilience scale compared to girls, both among sexual abuse victims and non-victims. Mediation analysis suggested that self-esteem fully mediates the impact of sexual abuse on resilience in boys, and that self-esteem partially mediates the impact of sexual abuse on resilience in girls. The results of the study demonstrated that sexual abuse negatively affects resilience and that the relationship between self-esteem and resilience interacts with gender. Furthermore, self-esteem is an essential factor for developing resilience following experience of sexual abuse. Keywords: resilience, sexual abuse, self-esteem, adolescents Kynferðisofbeldi hefur alvarleg áhrif á fórnarlömb en þó virðast einhver fórnarlömb sýna ótrúlega hæfni til að viðhalda eðlilegri virkni, eða seiglu. Rannsóknir á brotaþolum kynferðisofbeldis gefa til kynna að margvíslegir einstaklings- og umhverfisþættir hafa áhrif á það hvernig seigla þróast hjá þeim sem hafa orðið fyrir kynferðisofbeldi. Markmið þessarar rannsóknar var að kanna áhrif kynferðisofbeldis á seiglu og hvernig sjálfsálit hefur áhrif á sambandið þar á milli. Rannsóknin notaðist við slembiúrtak sem samanstóð af 2.129 ...